Comparative study of the possibility of interdental papilla reconstruction using connective tissue graft with and without Emdogain - Soleymani Shayesteh Y.; Khorsand A.; Habibi B. (Tehran University of Medical Sciences, 2008)
Background and Aim: Improving esthetics is a major goal in periodontal treatments and specially reconstruction of dental papilla is of great importance. Different techniques have been developed, however the results are not completely predictable. The aim of the present study was to compare the possibility of papilla reconstruction using connective tissue graft with and without Emdogain.Materials and Methods: In this clinical trial, 40 class II lost interdental papilla (Nordland- Tarnow classification) in 18 patients (4 male and 14 female) were studied. Samples were randomly devided into two groups. Case group was treated by connective tissue graft and emdogain (Straumann-USA) and controls were treated using connective tissue graft only. Periodontal parameters including papilla height (PH), periodontal pocket depth (PPD) and clinical attachment level (CAL) were measured before surgery, and 3 and 6 months after treatment. At the tenth days and 1 month after treatment only the papilla height was measured. Repeated measures analysis was used for data analysis with p<0.05 as the level of significance.Results: In the control group the mean papilla height changed from 3.38 0.89 to 2.85 0.93 on the 3rd month and 2.90 0.95 on the 6th month. The mean PPD changed from 2.8  0.68 to 2.55 0.70 on the 3rd month and 3.06 1.25 on the 6th month. The mean CAL changed from 3.88 1.29 to 3.79 1.25 on the 3rd month and 4.11 1.44 on the 6th month. In test group the mean papilla height changed from 2.98 0.91 to 2.45 1.55 on the 3rd month and 2.55 1.48 on the 6th month. The mean PPD changed from 2.75 1.49 to 2.63 1.38 on the 3rd month and 2.88 1.39 on the 6th month. The mean CAL changed from 3.75 1.24 to 4.01 1.45 on the 3rd month and 4.28 1.63 on the 6th month. These differences were not significant between the studied groups (P>0.05).Conclusion: Based on the results of this study, use of connective tissue with or without emdogain is not effective in interdental papilla reconstruction.